The Issue of Balancing Internal Combustion Engines with Non-Conventional Crank Mechanism - Baran, Peter; Kukuca, Pavol; Barta, Dalibor; Labuda, Robert; Drozdiel, Pawel; Pukalskas, Saugirdas (Communications - Scientific letters of the University of Zilina, 2017)
It is possible to use not only classical crank mechanisms, but also non-conventional mechanisms in design of combustion engines. Balancing these mechanisms is a fundamental prerequisite of their proper function and long life. The concept of measuring system for balancing analysis is applied to a special type of piston machines with wobble mechanism. First part of the paper deals with description of FIK nonconventional mechanism (named after the inventors Fitz, Istenik, Kukuca), main parts and its functionality. Second part deals with measuring system, which is designed to measure dynamic parameters of non-conventional piston mechanism. The measuring system concept is applied to a special type of piston machines with wobble board. Analysis compares the three basic states, without balancing mass and with first and second type of balancing mass. Balancing system is determined from the calculation of the dynamical model. Design of balancing system and placement of sensor for acceleration measurement corresponds to the constructional possibilities of prototype model FIK.